2001
DOI: 10.1007/s11661-001-0107-9
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of creep deformation and fracture behavior of 2.25Cr-1Mo similar and dissimilar weld joints

Abstract: The evaluation of the creep deformation and fracture behavior of a 2.25Cr-1Mo steel base metal, a 2.25Cr-1Mo/2.25Cr-1Mo similar weld joint, and a 2.25Cr-1Mo/Alloy 800 dissimilar weld joint at 823 K over a stress range of 90 to 250 MPa has been carried out. The specimens for creep testing were taken from single-V weld pads fabricated by a shielded metal arc-welding process using 2.25Cr-1Mo steel (for similar-joint) and INCONEL 182 (for dissimilar-joint) electrodes. The weld pads were subsequently given a postwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 6 publications
2
31
0
Order By: Relevance
“…It has recently been suggested 13 that martensite formation can be avoided in DMWs by careful control over the welding parameters so that the cooling rate is low enough to avoid martensite formation within the concentration gradient of the PMZ. Unfortunately, no detailed microstructural information was provided to support this claim, and this is not consistent with the large body of experimental evidence 8,9,12,14,15,16,17,18,19 that clearly shows martensite will always form under the combination of composition and cooling rate associated with practical welding conditions. …”
Section: As-welded Conditionmentioning
confidence: 89%
See 4 more Smart Citations
“…It has recently been suggested 13 that martensite formation can be avoided in DMWs by careful control over the welding parameters so that the cooling rate is low enough to avoid martensite formation within the concentration gradient of the PMZ. Unfortunately, no detailed microstructural information was provided to support this claim, and this is not consistent with the large body of experimental evidence 8,9,12,14,15,16,17,18,19 that clearly shows martensite will always form under the combination of composition and cooling rate associated with practical welding conditions. …”
Section: As-welded Conditionmentioning
confidence: 89%
“…Thus, thermal cycling can intensify this factor. Recent experimental studies 8,34 have confirmed that most of the strain that occurs during creep deformation is associated with the localized strain near the interface. Figure 23 shows results from an instrumented creep test on a weld involving 2.25Cr-1Mo steel and Inconel 82 filler metal where the extension was measured globally (i.e., within the entire gage length) and locally along the interface.…”
Section: Failure Mechanism Of Dmwsmentioning
confidence: 97%
See 3 more Smart Citations